The effects of organic matter and anaerobic oxidation of methane on the microbial sulfate reduction in cold seeps - Sun, Tiantian; Wu, Daidai; Wu, Nengyou; Yin, Ping (Frontiers in Marine Science, 2023)
Cold seep sediments are dominated by intensive microbial sulfate reduction coupled to anaerobic oxidation of methane. Through geochemical measurements of pore water with methane seep sediments collected from South China Sea, we provide insight into the role of organic matter in methane seep sediments. Pore water data combined with PROFILE model showed co-occurring microbial organoclastic sulfate reduction and anaerobic oxidation of methane coupled with sulfate reduction. Besides, positions of sulfate methane transition zone are approximately ~400 to 800 centimeters below seafloor. From fluxes of sulfate and methane as well as oxygen and sulfur isotopes of the residual sulfate pool, it can be said that microbial sulfate reduction in sediments is mainly controlled by intense anaerobic oxidation of methane, but there is a certain relationship with organic matter metabolism process. Considering different intensities of methane seepages, in addition to oxidation of H2S and disproportionation of S intermediates, organoclastic sulfate reduction also play an important role in sulfur isotope fractionation. Evidence from Rayleigh fractionation approach shows that the sulfur and oxygen isotopes in the residual sulfate pool between organoclastic sulfate reduction and anaerobic oxidation of methane are significantly different, which are mainly affected by sulfate reduction rate and sulfur disproportionation in different degrees. These results highlight a role for organic matter during microbial sulfate reduction in cold seeps. This emphasizes that traditional redox order of bacterial respiration is highly simplified, where, in sediments such as these seeps, all of these microbial sulfate reduction processes can occur together with complex couplings between them.